Antimicrobial Resistance Policy Protagonists and Processes—A Qualitative Study of Policy Advocacy and Implementation - Chan, Olivia S. K.; Lam, Wendy W. T.; Fukuda, Keiji; Tun, Hein Min; Ohmagari, Norio; Littmann, Jasper; Zhou, Xu Dong; Xiao, Yonghong; Liu, Ping; Wernli, Didier (Antibiotics, 2022)
Antimicrobial resistance (AMR) fundamentally weakens societal foundations economically and in health care. The development of well-considered policies against AMR is important. However, in many places, AMR policy implementation remains elusive. This study aims to identify enablers and deterrents as well as processes and conditions in AMR policy advocacy. It also aims to identify AMR implementation conditions where AMR national policies are adopted and, to a certain extent, formulated and implemented. This study adopts qualitative research methodology and applies the Grounded Theory Framework to identify thematic findings from interviews conducted in China, Japan, Norway, the United Kingdom (UK), and the United States of America (US). It was identified that AMR policy protagonists are critical to filtering AMR issues and identifying policies “fit to prioritize” and “fit to implement”. They have helped move policy prioritization needles in the UK and the US and engaged in diplomatic efforts in the UK. In these cases, no clientelism was considered. In the US, protagonists who talked to the right decision-makers in the right office at the right time both moved AMR issues from individuals to institutional agenda and from social norms to policy agenda. To conclude, there are three thematic policy conditions that are significant to AMR policy advocacy and implementation: committed personal championship, institutionalization of policies, and social norms facilitate AMR policy advocacy and implementation.